Influence of Cultural Values on Emotion Regulation and Well-Being: A Study of Thai University Students - Zohar, Shimon (Scholar: Human Sciences, 2014)
Several strategies can be employed in face of an event that requires one to change the resulting emotion. It was suggested that the choice of a strategy is influenced by one’s culture and may also influence one’s well-being (Matsumoto, 2007). Findings demonstrate that in response to emotional eliciting event individuals of Asian cultures do not exhibit emotion that may disrupt the status-quo. This suppression of emotion was found to be detrimental to one’s well-being. Poles apart, when facing a similar event, individuals of American and European cultures change the way they think about the event. This reappraisal of the event was found to be beneficial to one’s well-being (Gross & John, 2003). In line with recent studies that suggest suppression may not be detrimental to well-being when it takes place in a culture where it is the norm, the purpose of the current study was to examine the influence of Thai cultural values on the choice of an emotion regulation strategy and well-being. Lack of instruments that allow the measurement of these variables for the Thai population, a preliminary study that consisted of a translation and validation of suitable instruments was performed. Results demonstrate the specific characteristics of Thai cultural values and cognitive emotion regulation strategies. While suppression was found to have a detrimental influence on well-being it was relatively minor, therefore suggesting that cultural norms do in fact play a role in this process.